检测PD-L1+循环肿瘤细胞的试剂在筛选癌症风险个体以及在癌症患者预后中的应用 (2023)
本发明公开了检测PD-L1<supgt;+</supgt;循环肿瘤细胞的试剂在制备筛选处于发生复发性或转移性癌症风险中的个体的试剂或试剂盒中的应用。本发明还公开了检测PD-L1<supgt;+</supgt;循环肿瘤细胞的试剂在制备预测癌症患者的预后的试剂或试剂盒中的应用。 Disclosed is a method for identifying a subject at risk of developing a recurrent or metastatic cancer, comprising detecting PD-L1 + circulating tumor cells in a blood sample, a tissue fluid sample or a specimen of the subject. Also disclosed is method for treating a cancer comprising identifying a subject having one ore more PD-L1 + circulating tumor cells by detecting PD-L1 + circulating tumor cells in a blood sample, a tissue fluid sample or a specimen of the subject, and administering a treatment to the subject.